2019
DOI: 10.1002/ehf2.12395
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest in Wilson's disease after curative liver transplantation: a life‐threatening complication of myocardial copper excess?

Abstract: We report the case of a 38‐year‐old man who presented with cardiac arrest 1 year after curative liver transplantation for Wilson's disease. Clinical work‐up proofed myocardial copper and iron accumulation using mass spectrometry, which led most likely to myocardial fibrosis as visualized by cardiovascular magnetic resonance (unprecedented delayed enhancement pattern) and endomyocardial biopsy. Consequently, cardiac arrest due to ventricular fibrillation and subsequent episodes of sustained ventricular tachycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Biomedicines 2021, 9, x FOR PEER REVIEW 3 of 26 Wilson's disease (WD) is a multisystemic disorder with variable symptoms characterized by abnormal deposits of copper. Clinical signs depend on the organs where copper is accumulated over the course of the pathological process (Figure 1; reviewed in [4][5][6]).…”
Section: Clinical Picture Of Wilson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Biomedicines 2021, 9, x FOR PEER REVIEW 3 of 26 Wilson's disease (WD) is a multisystemic disorder with variable symptoms characterized by abnormal deposits of copper. Clinical signs depend on the organs where copper is accumulated over the course of the pathological process (Figure 1; reviewed in [4][5][6]).…”
Section: Clinical Picture Of Wilson's Diseasementioning
confidence: 99%
“…Further studies revealed that cardiac manifestations are relatively frequent and can be life-threatening. In fact, cardiac arrest can occur even in liver-transplanted patients [26]. Therefore, in the diagnosis and the follow-up of WD patients, tests such as electrocardiogram, cardiac biomarkers, echocardiography, and 24-h Holter monitoring should be included [27].…”
Section: Additional Clinical Manifestationsmentioning
confidence: 99%
“…The autopsy was not able to explain the reasons for death, and did not document any organic lesion. Hence, ventricular fibrillation was suspected to be responsible for the sudden unexplained death, as reported presciently 28 …”
Section: Resultsmentioning
confidence: 89%
“…Despite a 6‐year treatment with d ‐penicillamine, he developed cardiomyopathy and congestive HF that was refractory to medical therapy and that led to his death. More recently, cardiac arrest was reported in a 38‐year‐old man, 1 year after curative liver transplantation for WD 28 . The patient presented with ventricular fibrillation requiring advanced cardiopulmonary resuscitation and four defibrillations.…”
Section: Resultsmentioning
confidence: 99%
“…Because the latter is associated with an overall increased risk for HF and death, dedicated cardiac care is required. In fact, a recent case report on a patient with sudden cardiac death in Wilson Disease, associated with LGE, underscores the role of fibrosis as a potentially critical marker in WD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%